2022
DOI: 10.1021/acsomega.2c00154
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Insight into the SARS-CoV2 Spike–ACE2 Interaction and Its Modulation by Hepcidin through a Multifaceted Computational Approach

Abstract: At the center of the SARS-CoV2 infection, the spike protein and its interaction with the human receptor ACE2 play a central role in the molecular machinery of SARS-CoV2 infection of human cells. Vaccine therapies are a valuable barrier to the worst effects of the virus and to its diffusion, but the need of purposed drugs is emerging as a core target of the fight against COVID19. In this respect, the repurposing of drugs has already led to discovery of drugs thought to reduce the effects of the cytokine storm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…From the theoretical perspective (in chronological order), the RBD-ACE2 and RBD-binders’ biological interfaces for the SARS-CoV-2 wt were investigated at the beginning of the COVID19 pandemic by Giron and colleagues and followed by several other works (e.g., refs , , , , and ). In the study carried out by Giron and coauthors, it was demonstrated using a constant-pH coarse-grained model and Monte Carlo (MC) simulations that the RBD of SARS-CoV-2 wt could bind to ACE2 with similar binding affinities to SARS-CoV-1.…”
Section: Introductionmentioning
confidence: 99%
“…From the theoretical perspective (in chronological order), the RBD-ACE2 and RBD-binders’ biological interfaces for the SARS-CoV-2 wt were investigated at the beginning of the COVID19 pandemic by Giron and colleagues and followed by several other works (e.g., refs , , , , and ). In the study carried out by Giron and coauthors, it was demonstrated using a constant-pH coarse-grained model and Monte Carlo (MC) simulations that the RBD of SARS-CoV-2 wt could bind to ACE2 with similar binding affinities to SARS-CoV-1.…”
Section: Introductionmentioning
confidence: 99%
“…refs. 24,[41][42][43][44][45][46][47][48][49] ). In the study carried out by Giron and co-authors, it was demonstrated using a constant-pH coarse-grained model and Monte Carlo (MC) simulations that the RBD of SARS-CoV-2 wt could bind to ACE2 with similar binding affinities to SARS-CoV-1.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, the COVID-19 pandemic prompted a multitude of investigations on the pathogeny of this new virus and also on the patent neurological disturbances shown in a series of cases, the infamous ”long COVID” [ 208 ] and its co-involvement with the RAS system [ 209 ]. A series of experimental results demonstrated that SARS-CoV-2 penetration is made at the level of the ACE receptor, mediated through the spike protein [ 210 ] connecting with the ACE2 receptor in the presence of calcium [ 211 ]. The deleterious effects on the CNS are similar to viral encephalitis or systemic inflammation, but some suspect an involvement of protein misfolding with an evolution towards NDG disease, with cognitive deficiencies or motor deficits [ 212 , 213 ].…”
Section: Renin-angiotensin-aldosterone System and Prion Diseasementioning
confidence: 99%